Perceived Impact of Healthcare Relationships and Interactions on Parental Experiences of Prenatal Diagnosis and Termination of Pregnancy for Foetal Anomaly on the Island of Ireland - Suzanne Heaney; Mark Tomlinson; Áine Aventin (Wiley, 2024)
ABSTRACT Objective The aim of this study was to explore parents' experiences of their relationships and interactions with healthcare professionals (HCPs) during care related to prenatal diagnosis and termination of pregnancy for foetal anomaly (TOPFA). Methods A qualitative approach was used. Participants included 33 parents (23 women and 10 men) from Northern Ireland (n = 11) and Ireland (n = 22) who had a TOPFA. Data collection methods included semi‐structured interviews and written narrative accounts. Data were analysed using thematic analysis. Results Findings confirmed that TOPFA was a traumatic, life‐altering experience for parents, impacting their health and well‐being. The actions, behaviours and words of HCPs impacted how parents perceived and interpreted their healthcare experiences and their access to services and supports. In relation to this, five themes are presented: (1) the importance of compassionate and non‐judgemental care, (2) the value of effective information and communication, (3) the desire for compassionate care for baby and facilitation of memory making, (4) the need for continuity of care and (5) parents' experiences of healthcare relationships during times of legislative change. Conclusion This research reveals the important role HCPs play in helping parents cope with prenatal testing and TOPFA. Parents who had a positive relationship with an HCP, in which information was communicated effectively and compassionate and non‐judgmental care was provided, felt more supported and more able to accept and adapt to their loss. Patient and Public Contribution An advisory group composed of parents who had experienced TOPFA and HCPs with experience in caring for such families were involved in the study from the outset, contributing to the design and development of data collection materials, interpretation of the findings and design of dissemination materials.